2004
DOI: 10.1103/physrevd.69.114007
|View full text |Cite
|
Sign up to set email alerts
|

RadiativeBdecays to the axialKmesons at next-to-leading order

Abstract: We calculate the branching ratios of B → K 1 γ at next-to-leading order (NLO) of α s where K 1 is the orbitally excited axial vector meson. The NLO decay amplitude is divided into the vertex correction and the hard spectator interaction part. The one is proportional to the weak form factor of B → K 1 transition while the other is a convolution between light-cone distribution amplitudes and hard scattering kernel. Using the light-cone sum rule results for the form factor, we have B(B 0 → K 0 1 (1270)γ) = (0.828… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…P B1 → P B9,10 → P B5,6 4. P B2 → P B9,10 → P B5, 6 We show also that these trajectories pass well from the radiationlike matter era to the dark energy-dominaed era (as ΛCDM cosmological model), as one can see in Figs. 3-5.…”
Section: ω = 5 Casesupporting
confidence: 70%
See 3 more Smart Citations
“…P B1 → P B9,10 → P B5,6 4. P B2 → P B9,10 → P B5, 6 We show also that these trajectories pass well from the radiationlike matter era to the dark energy-dominaed era (as ΛCDM cosmological model), as one can see in Figs. 3-5.…”
Section: ω = 5 Casesupporting
confidence: 70%
“…P A1 → P A5,6 2. P A2,3 → P A5, 6 It is shown that the paths in a phase space pass well from the radiation-like matter era to dark energy-dominated era of the Universe, as one can see in Figs. 1 and 2.…”
Section: ω = −3 Casementioning
confidence: 68%
See 2 more Smart Citations
“…Let's add that multiple field scalar-tensor has been studied before [8][9][10][11][12][13][14][15][16][17][18][19]. Triplet scalar field in the context of global monopole has been studied extensively in literature [20][21][22][23][24][25][26][27][28][29]. One has to keep in order that the single scalar field coupled with gravity has been studied more rigorously.…”
Section: Introductionmentioning
confidence: 99%